Traumaattinen muisti nykyproosassa - Jytilä, Riitta (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2022)
This is the first study to examine Finnish trauma fiction in detail. The book discusses the novels of Katja Kettu, Sofi Oksanen, Elina Hirvonen and Emmi Itäranta, where historical and collective traumas meet stories of personal vulnerability. Traumatic Memory in Contemporary Prose Fiction addresses war traumas and marks left by terrorism, colonialism, domestic violence and sexual violence, and analyses the aspects of ecological trauma and future threats. The study combines the latest discussions on cultural memory studies and trauma theory with critical perspectives offered by feminist criticism and research in transnationalism. It illustrates how cultural narratives, literary conventions and aesthetic strategies regulate and produce traumatic experiences. Traumatic memory is not only a phenomenon dealing with the past, but it involves a wide range of individual, cultural, ecological, political and economic dimensions.